Family Business Iatrogenesis - Montiel Méndez, Oscar Javier; Soto Maciel, Argentina (Cooperativismo & Desarrollo, 2024)
Focusing on different viewpoints on the dark side of entrepreneurship (DSE), this study aims to relate the potential elements identified as family business iatrogenesis (FBI), where these elements can put the family business (FB) at risk, which is suggested to be a contribution to FB studies, a novel perspective. Literature on entrepreneurship and FB was selected and analyzed according to the “dark side” framework using a scoping review method. The results suggest that many perspectives remain for research, starting with a clarification and a more precise definition, not only of the construct itself but also of the forces that drive this dark side, which can develop FBI and the metastasis of the FB. This study has implications for the development of public policies, the creation of family business training programs at various levels, public policies aimed at FB, small, medium, and large companies, government and universities, entrepreneurial families, and, generally, the entrepreneurial ecosystem to establish strategies that can anticipate and address it to prevent a potential discontinuity of FB, given the current state of most economies.